An in vitro genotoxicity study of silver amalgam on Ames test - Akram Hassan; S.A Omar; Zaihan Ariffin (Fakultas Kedokteran Gigi, Universitas Gadjah Mada, 2010)
Silver amalgam/Silverfil Argentum® is a ‘Malaysian made amalgam’ has already been approved to be free from cytotoxicity, however its genotoxic effect has not been explored yet as biocompatible material. The objective of this study was to identify the genotoxic characteristic of silver amalgam by using Bacterial Reverse Mutation Assay (Ames test). This was a descriptive experimental study involving one strain of mutated Salmonella. The test material was evaluated in one mutated strain of Salmonella typhimurium TA1538 with and without an external metabolic activation system (S9 Mix). The bacteria were incubated for 48 hours at 37±0.5ºC before the colony growth or revertant colonies were counted. Data obtained were analyzed by using non-statistical method. The investigation of the genotoxic reaction on the test material revealed thatthe number of revertant colonies in both strains with and without S9 Mix were less than twice of the negative control even in the presence of high silver amalgam concentrations (5.0μg/ml). This study demonstratedthat the test material did not exhibit any mutagenic activity under the chosen conditions. Thus, silver amalgam could be considered to have no genotoxicity effect.